Entrepreneurship Education and Other Exogenous Variables in the Theory of Planned Behavior Model: A Systematic Literature Review - Rustiana (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: The aim of the study is to: 1) identify the role entrepreneurship education (EE) in the theory of planned behavior (TPB) model, and how it enhances students’ entrepreneurship intention (EI), 2) identify various other exogenous variables commonly paired with EE that increase EI, 3) map the various roles of EE and the exogenous variables in improving students’ EI into a single model. Background Problems: What is the role of entrepreneurship education and the exogenous variables in the TPB model, and how do they increase students’ entrepreneurship intention? Novelty: This paper’s novel contributions include 1) filling the knowledge gap in the field of entrepreneurship related to the TPB model, 2) proposing a map to depict the integration of EE and other exogenous variables into the TPB model, to make one comprehensive model. Research Methods: The data sets were drawn from the Scopus database with a systematic literature review approach, with a protocol that used the keywords "entrepreneurship education," "entrepreneurial education," and "TPB." The protocol found 108 articles in the Scopus database, published between 2006 and 2023, which were extracted. Then, the articles underwent further analysis using exclusion and inclusion criteria, resulting in 24 articles that met our requirements. Quantitative and qualitative analysis were then carried out, using statistical descriptive and bibliometric analysis. Finding/Results: This study shows that entrepreneurship education and the exogenous variables that influence entrepreneurship intention in the TPB model have various roles. Conclusion: The results expose critical research gaps and the need to develop new theoretical frameworks that combine and extend the TPB model with other relevant variables in higher education.